Influence of Service Quality, Price, Promotion and Loyalty Through Satisfaction Lazada Semarang - Ratnasari, Maria Gratia Adi; Wibowo, Estri Ayu; Soesanto, Harry (Economic and Business Horizon, 2025)
This study aims to evaluate the influence of price perception, service quality, and promotion on Lazada customer loyalty in Semarang, with customer satisfaction as a mediating variable. This study is motivated by the results of previous studies that showed inconsistent findings regarding the relationship between these variables. Using a quantitative approach and survey method, data were collected through questionnaires distributed to 100 active Lazada users in Semarang, who were selected randomly. Data analysis was carried out using the Partial Least Squares - Structural Equation Modeling (PLS-SEM) technique using SmartPLS software. The results showed that service quality, fair price perception, and promotion have a positive influence on customer satisfaction. In addition, satisfaction was shown to play a significant mediating role in strengthening customer loyalty. These findings highlight the importance of integrating digital transformation and sustainable marketing in building a valuable customer experience. The strategic implications of this study provide direction for Lazada to increase retention and loyalty through quality service, competitive prices, and relevant and socially responsible promotional communications.